142 On-demand palliative care for lung cancer patients: A multi-disciplinary out-patient clinic. (14th March 2023) - Sutton, Sue; Bonwick, Helen
Abstract : Background: The Rapid access lung cancer clinic incorporates a multi-disciplinary team approach including surgeons, respiratory physicians, oncologists, radiologists, specialist nurses and specialist palliative care. We have developed a unique approach which combines medical and therapy palliative care assessments in a single out-patient appointment. Evidence suggests that taking a multi-disciplinary approach can improve patient care1, 2. Methods: Patients attending the out-patient clinic are referred to the Specialist Palliative Care Team (SPCT) and Occupational Therapist (OT) at diagnosis or at any point of their disease trajectory. A joint approach to the assessment incorporates psychological and spiritual needs, social needs, family support needs and activities of daily living as well as establishing what is important to the patient. If it is identified that a community visit would be helpful, this is implemented by the OT without the need to duplicate an initial assessment. Further needs highlighted at home are addressed by the OT with onward referral to the appropriate service as required. This joint clinic also enables pharmacological and non-pharmacological dyspnoea management which has been evidenced as the optimal approach3. Results: Results are positive with patients and families reporting that they feel well supported both in clinic and at home. Feedback suggests that patients feel comfortable and confident in contacting the team for follow up as required. The physician and OT provide a unique 'on-demand' service which allows patients to return to clinic or request further OT home visits as required. Conclusions: This unique approach to providing palliative care for lung cancer patients has proven beneficial for a number of reasons. Symptoms such as pain, nausea and psychological distress are addressed alongside functional needs such as mobility issues, social isolation and activities of daily living. Our work demonstrates how combining medical and therapy assessments can help to provide holistic care to patients with lung cancer. References: Kochovska S, et al . Earlier multidisciplinary palliative care intervention for people with lung cancer: a systematic review and meta-analysis. Translational Lung Cancer Research, 2020;9 (4):1699–1709. Nottleman L, et al . A new model of early, integrated palliative care: palliative rehabilitation for newly diagnosed patients with non-resectable cancer. Supportive Care in Cancer, 2019;27 :3291–3300 Chin C, Booth S. Managing breathlessness: a palliative care approach. Postgrad Med J 2016;92 :393–400.